Ameliorative effects of the traditional Chinese medicine formula Qing-Mai-Yin on arteriosclerosis obliterans in a rabbit model - Lei Zhang; Jia-Qin Yuan; Fu-Chen Song; Mei-Dong Zhu; Qi Li; Sheng-Hua Liu; Kai Zhao; Cheng Zhao (Taylor & Francis Group, 2020)
Context Qing-Mai-Yin (QMY) is a clinically used herbal formula for treating arteriosclerosis obliterans (ASO). Objective To evaluate the chemical constituents and effects of QMY on ASO rabbit model. Materials and methods Forty-eight New Zealand rabbits were divided into six groups (n = 8): normal (normal rabbits treated with 0.5% CMC-Na), vehicle (ASO rabbits treated with 0.5% CMC-Na), positive (simvastatin, 1.53 mg/kg), and QMY treatment (300, 600, and 1200 mg/kg). ASO rabbit model was prepared by high fatty feeding, roundly shortening artery, and bovine serum albumin immune injury. QMY (300, 600 and 1200 mg/kg) was orally administered for 8 weeks. The effects and possible mechanisms of QMY on ASO rabbits were evaluated by pathological examination, biochemical assays, and immunohistochemical assays. The compositions of QMY were analysed using HPLC-Q-TOF-MS/MS analysis. Results Compared to the vehicle rabbit, QMY treatment suppressed plaque formation and intima thickness in aorta, and decreased intima thickness, whereas increased lumen area of femoral artery. Additionally, QMY treatment decreased TC, TG and LDL, decreased CRP and ET, and increased NO and 6-K-PGF1α in serum. Furthermore, the potential mechanisms studied revealed that QMY treatment could suppress expression of TNF-α, IL-6, ICAM-1 and NF-κB in endothelial tissues, and increase IκB. In addition, HPLC analysis showed QMY had abundant anthraquinones, stilbenes, and flavonoids. Conclusion QMY has ameliorative effects on ASO rabbit, and the potential mechanisms are correlated to reducing inflammation and down-regulating NF-κB. Our study provides a scientific basis for the future application and investigation of QMY.